Aloxe3 knockout mice reveal a function of epidermal lipoxygenase-3 as hepoxilin synthase and its pivotal role in barrier formation - Krieg, Peter; Rosenberger, Sabine; Juanes, Silvia de; Latzko, Susanne; Hou, Jin; Dick, Angela; Kloz, Ulrich; van der Hoeven, Frank; Haußer-Siller, Ingrid; Esposito, Irene; Rauh, Manfred; Schneider, Holm (The journal of investigative dermatology, 2013)
Loss-of-function mutations in the lipoxygenase (LOX) genes ALOX12B and ALOXE3 are the second most common cause of autosomal recessive congenital ichthyosis. The encoded proteins, 12R-LOX and epidermal LOX-3 (eLOX-3), act in sequence to convert fatty acid substrates via R-hydroperoxides to specific epoxyalcohol derivatives and have been proposed to operate in the same metabolic pathway during epidermal barrier formation. Here, we show that eLOX-3 deficiency in mice results in early postnatal death, associated with similar but somewhat less severe barrier defects and morphological changes than reported earlier for the 12R-LOX-knockout mice. Skin lipid analysis demonstrated that the severity of barrier failure is related to the loss of covalently bound ceramides in both 12R-LOX- and eLOX-3-null mice, confirming a proposed functional linkage of the LOX pathway to ceramide processing and formation of the corneocyte lipid envelope. Furthermore, analysis of free oxygenated fatty acid metabolites revealed strongly reduced levels of hepoxilin metabolites in eLOX-3-deficient epidermis, indicating an additional function of eLOX-3 in mammalian skin as a hepoxilin synthase linked to the 12S-LOX pathway.
Published online 26 July 2012
Gesehen am 31.03.2021